Gestión administrativa – financiera y su impacto en la toma de decisiones en la Cooperativa de Ahorro y Crédito “Sinchi Runa” cantón La Maná en el periodo 01 de enero al 31 de diciembre del 2012 - Ramos Herrera, Mónica Gabriela (2015)
Administrative management of the Cooperative Financial "SinchiRuna" is the point of analysis of this researchand over these results measure the impact that causes in making decisionsfor which internal control is analyzed and described the entire operation of the cooperative, thendetailed the functions of each department as well as employees that working in its measuring the efficiency and effectiveness for the job, usedindicators of Financial management administrative system. Applingsome instruments to collect data, we can mention the surveys partners and operational staff at the same time the interview to the manager.